Rejection, Current Suffering in the Lives of People with HIV/AIDS: A Qualitative Study in Iran - Mansoureh Ashghali Farahani; Armin Zareian; Maryam Khoshbakht-Pishkhani; Mehrnoosh Khoshtrash (Caspian Journal of Health Research, 2024)
Background: People with HIV/AIDS face numerous challenges, including the effect of the disease on their personal relationships with family, friends, colleagues, and healthcare professionals. The purpose of this qualitative study was to investigate social interactions among patients with HIV/AIDS.